2005
DOI: 10.1162/105474605774918679
|View full text |Cite
|
Sign up to set email alerts
|

Successes and Failures in Co-Present Situations

Abstract: Virtual environments systems based on immersive projection technologies (IPTs) offer users the possibility of collaborating intuitively in a 3D environment. While considerable work has been done to examine interaction in desktop-based collaborative virtual environments (CVEs), there are currently no studies for collaborative interaction using IPTs.The aim of this paper is to examine how immersive technologies support interaction and to compare this to the experience with desktop systems. A study of collaborati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…One departure point for the development of this analysis method is that interaction in CVEs is often fragmented interaction (Hindmarsh, Fraser, Heath, Benford, & Greenhalgh, 1998); that is, collaboration is frequently interrupted by lack of awareness of what the other person is doing, by insufficient feedback to one's action from the other person(s), and especially by difficulty in seeing what the other is seeing (see also Hindmarsh, Fraser, Heath, & Benford, 2002). Another background is the fact that the ways in which interaction is made difficult in collaborative desktop environments should not necessarily apply to immersive environments-because here users have a better view of the other person, of how they react to one's movements, and a better field of view for seeing what the other person is seeing (Heldal, Steed, Spante, Schroeder, Bengtsson, & Partanen, 2005).…”
Section: Methods 2: Analysis Of Interaction Fragmentsmentioning
confidence: 99%
“…One departure point for the development of this analysis method is that interaction in CVEs is often fragmented interaction (Hindmarsh, Fraser, Heath, Benford, & Greenhalgh, 1998); that is, collaboration is frequently interrupted by lack of awareness of what the other person is doing, by insufficient feedback to one's action from the other person(s), and especially by difficulty in seeing what the other is seeing (see also Hindmarsh, Fraser, Heath, & Benford, 2002). Another background is the fact that the ways in which interaction is made difficult in collaborative desktop environments should not necessarily apply to immersive environments-because here users have a better view of the other person, of how they react to one's movements, and a better field of view for seeing what the other person is seeing (Heldal, Steed, Spante, Schroeder, Bengtsson, & Partanen, 2005).…”
Section: Methods 2: Analysis Of Interaction Fragmentsmentioning
confidence: 99%
“…desktop) CVE systems could be alleviated by ICVEs due to intuitive body tracking and the larger field-of-view [12]. Later studies have shown this to be the case, but there are still problems due to the representation of avatars: in particular, gaze is identified as an important cue not captured or transmitted faithfully by the medium [11]. Figure 1 illustrates the ability for unconstrained movement in a shared virtual space while maintaining meaningful gaze as supported by EyeCVE.…”
Section: Collaborative Virtual Environments and Avatarsmentioning
confidence: 99%
“…Results indicated that distance judgments after using the virtual reality system was short compared to real life training. e) Heldal, Steed, Spante, & Schroeder (2005): An exploratory study was performed where 6 pairs of participants were asked to use a virtual environment. Each member of a pair was in a different location.…”
Section: Evaluation Instrumentsmentioning
confidence: 99%